Amylose/cellulose nanofiber composites for all-natural, fully biodegradable and flexible bioplastics. (1st February 2021) - Xu, Jinchuan; Sagnelli, Domenico; Faisal, Marwa; Perzon, Alixander; Taresco, Vincenzo; Mais, Marco; Giosafatto, Concetta Valeria L.; Hebelstrup, Kim H.; Ulvskov, Peter; Jørgensen, Bodil; Chen, Ling; Howdle, Steven M.; et al.
Highlights: Engineered amylose and waste CNF generate good bioplastics. CNF enhanced crystallinity, mechanics and permeability. Cellulose nanofibers and amylose showed domain phase separation. Abstract: Thermoplastic, polysaccharide-based plastics are environmentally friendly. However, typical shortcomings include lack of water resistance and poor mechanical properties. Nanocomposite manufacturing using pure, highly linear, polysaccharides can overcome such limitations. Cast nanocomposites were fabricated with plant engineered pure amylose (AM), produced in bulk quantity in transgenic barley grain, and cellulose nanofibers (CNF), extracted from agrowaste sugar beet pulp. Morphology, crystallinity, chemical heterogeneity, mechanics, dynamic mechanical, gas and water permeability, and contact angle of the films were investigated. Blending CNF into the AM matrix significantly enhanced the crystallinity, mechanical properties and permeability, whereas glycerol increased elongation at break, mainly by plasticizing the AM. There was significant phase separation between AM and CNF. Dynamic plasticizing and anti-plasticizing effects of both CNF and glycerol were demonstrated by NMR demonstrating high molecular order, but also non-crystalline, and evenly distributed 20 nm-sized glycerol domains. This study demonstrates a new lead in functional polysaccharide-based bioplastic systems.